On the Use of Generative Deep Learning Approaches for Generating Hidden Test Scripts - Oz, Mert; Kaya, Caner; Olmezogullari, Erdi; Aktas, Mehmet S. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2021)
With the advent of web 2.0, web application architectures have been evolved, and their complexity has grown enormously. Due to the complexity, testing of web applications is getting time-consuming and intensive process. In today's web applications, users can achieve the same goal by performing different actions. To ensure that the entire system is safe and robust, developers try to test all possible user action sequences in the testing phase. Since the space of all the possibilities is enormous, covering all user action sequences can be impossible. To automate the test script generation task and reduce the space of the possible user action sequences, we propose a novel method based on long short-term memory (LSTM) network for generating test scripts from user clickstream data. The experiment results clearly show that generated hidden test sequences are user-like sequences, and the process of generating test scripts with the proposed model is less time-consuming than writing them manually.
Keywords: Test automation; test script generation; LSTM; clickstream data; web testing; INFORMATION; Computer Science; Engineering